Improving Intercultural Education at Chinese Institutions from German Experience - Huang, Lihe (Journal of International Students, 2015)
While flying on an airplane to Germany, heading to my new appointment as a visiting scholar, I reminded myself that there would likely be some cultural differences upon embarking on this new journey. But after I began my sojourn there, I still found myself surprised by the cultural shock I was experiencing. I had taken for granted that my English education and some reading on German culture and society could provide me adequate knowledge to get along with these “Westerners”.